Novel Screen-Printed Sensor with Chemically Deposited Boron-Doped Diamond Electrode: Preparation, Characterization, and Application - Matvieiev, Oleksandr; Šelešovská, Renáta; Vojs, Marian; Marton, Marián; Michniak, Pavol; Hrdlička, Vojtěch; Hatala, Michal; Janíková, Lenka; Chýlková, Jaromíra; Skopalová, Jana; Cankař, Petr; Navrátil, Tomáš (Biosensors, 2022)
New screen-printed sensor with a boron-doped diamond working electrode (SP/BDDE) was fabricated using a large-area linear antenna microwave chemical deposition vapor system (LA-MWCVD) with a novel precursor composition. It combines the advantages of disposable printed sensors, such as tailored design, low cost, and easy mass production, with excellent electrochemical properties of BDDE, including a wide available potential window, low background currents, chemical resistance, and resistance to passivation. The newly prepared SP/BDDEs were characterized by scanning electron microscopy (SEM) and Raman spectroscopy. Their electrochemical properties were investigated by cyclic voltammetry and electrochemical impedance spectroscopy using inner sphere ([Fe(CN)6]4-/3-) and outer sphere ([Ru(NH3)6]2+/3+) redox probes. Moreover, the applicability of these new sensors was verified by analysis of the anti-inflammatory drug lornoxicam in model and pharmaceutical samples. Using optimized differential pulse voltammetry in Britton-Robinson buffer of pH 3, detection limits for lornoxicam were 9 × 10-8 mol L-1. The oxidation mechanism of lornoxicam was investigated using bulk electrolysis and online electrochemical cell with mass spectrometry; nine distinct reaction steps and corresponding products and intermediates were identified.
Keywords: Oxidation-Reduction; Ramanova spektroskopie; elektrolýza; oxidace-redukce; Boron; bor; Electrolysis; elektrody; Electrodes; Spectrum Analysis, Raman